2018
DOI: 10.1002/mrm.27598
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid–suppressed T2‐weighted MR imaging at 7 T for human brain

Abstract: Purpose T 2 ‐weighted lesional imaging is most commonly performed using inversion recovery turbo spin echoes. At 7 T, however, this acquisition is limited for specific absorption rate and resolution. This work describes and implements a method to generate CSF‐suppressed T 2 ‐weighted imaging. Methods The strategy uses a driven equilibrium spin‐echo preparation within an inversion recovery with multiple 3D gradient‐ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…As a consequence, finding the balance between signal intensities across the brain may be subject to radiologic priorities, that is, whether a radiologist wants to focus on medial (prioritize low FA) or lateral (prioritize high FA) structures. These difficulties have led to research into new types of RF pulse strategies and sequence designs 24,25 to mitigate these problems.…”
Section: D Fluid Attenuation Inversion Recovery (Flair) Sequencementioning
confidence: 99%
“…As a consequence, finding the balance between signal intensities across the brain may be subject to radiologic priorities, that is, whether a radiologist wants to focus on medial (prioritize low FA) or lateral (prioritize high FA) structures. These difficulties have led to research into new types of RF pulse strategies and sequence designs 24,25 to mitigate these problems.…”
Section: D Fluid Attenuation Inversion Recovery (Flair) Sequencementioning
confidence: 99%
“…Other pathologies of a vascular nature, such as cerebral hemorrhage, thrombosed aneurysm, arteriovenous malformation, cavernoma, and microhemorrhage, are also seen in T2-weighted images [14] . Unfortunately, T2 is limited by the signal produced by CSF with partial volume effects and flow artifacts which significantly inhibit periventricular and subcortical brain region 4/14 https://www.doi.org/10.53964/jmmi.2023002 evaluation [15] . Within the spine, T2-weighted imaging is helpful in the detection and diagnosis of stenosis, nerve root compression, disc disease, or infection [16] .…”
Section: T2mentioning
confidence: 99%
“…Cerebrovascular disease: Cerebral blood flow in reversible cerebral ischemia has been investigated using 15 O-H 2 O PET and perfusion-weighted imaging (PWI) [68] . Adoption of PWI methods, including DSC and ASL, is still lacking for regular clinical usage due to the lack of consistency and unpredictability in the values the techniques produce.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While FDA approved 2D and 3D FLAIR T2WI sequences modified to stay within SAR, spatial and temporal limitations are available at 7T, the T2‐weighting is generally poor compared to 3 or 1.5T 2 . Innovative approaches currently in research/development that have been reported to improve T2WI and FLAIR‐T2WI include novel pulse sequences, such as gradient and spin echo, simultaneous multislice with power independent of number of slices, magnetization‐prepared fluid‐attenuated inversion recovery gradient‐echo approaches, 3D tailored RF pulses, and synthetic MR with deep learning reconstruction , 2,38,39 but to date, none are available as FDA‐approved sequences. For now, the use of 7T as the final tier in our multitier imaging strategy reduces the impact of this issue, because a combination of comparison 1.5T or 3T FLAIR T2WI images and 7T T2WI is generally sufficient to evaluate for transmantle sign and hippocampal edema/gliosis.…”
Section: T Artifacts and Challenges—siv And Signal Lossmentioning
confidence: 99%